Concept of Aging of Skin in Unani Medicine and its Management through Hydration therapy: A Review - FAIZ, ABUL; Anas, Mohammed (Journal of Drug Delivery and Therapeutics, 2019)
Unani medicine is based upon the theory of four humors in the body. The temperaments of individuals are revealed accordingly by the words sanguine, phlegmatic, choleric, and melancholic on the preponderance of the respective humor. Innate fluid (Ratoobat-e-ghareeziya) plays a key role in maintaining equilibrium of innate heat (Hararat-e-ghareeziya). Change in the quality and quantity of Ratoobat-e-ghareeziya, directly affects Hararat-e-ghareeziya. Excessive reduction (tahleel) in Hararat-e-ghareeziya affects in two ways; i.e. Diminished Hararat-e-ghareeziya causes change in physiological functions of the body like in case of skin, when innate fluid of diminished, the skin becomes cold and dry in temperament which leads to wrinkles and early aging of skin. Hydration is one of the important therapies to prevent early aging of skin. Recent studies also reveal that during the aging cell division in the skin, decreases reduce collagen production and change the elastin fibers of structure. The visible changes are a decrease in sebum production and the moisture content, which is why many elderly suffer from dry skin and decreased elasticity of the skin. The result is that the skin is flaccid and puckering. Other factors are your lifestyle, diet, heredity, and other personal habits like smoking can produce free radicals. Free radicals damage the cells, leading to premature wrinkles. This paper aims to present the concept of Aging of skin, prevention and basic principles of management. Keywords: Aging, Humors, Temperament